2007
DOI: 10.3113/fai.2007.0991
|View full text |Cite
|
Sign up to set email alerts
|

Minimally Invasive Calcaneo-Stop Method for Idiopathic, Flexible Pes Planovalgus in Children

Abstract: The 'calcaneo-stop' method is a simple, effective, minimally invasive technique for the treatment of idiopathic, flexible pes planus in carefully selected pediatric patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0
4

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(39 citation statements)
references
References 8 publications
1
34
0
4
Order By: Relevance
“…All patients included in this study have undergone the calcaneo-stop surgical procedure for anterograde screw implantation, which was previously described in detail in several papers [13][14][15][16]. Namely, in general or regional .…”
Section: Surgical Proceduresmentioning
confidence: 99%
“…All patients included in this study have undergone the calcaneo-stop surgical procedure for anterograde screw implantation, which was previously described in detail in several papers [13][14][15][16]. Namely, in general or regional .…”
Section: Surgical Proceduresmentioning
confidence: 99%
“…Vedantam et al [23] reported the application of polyethylene tarsal sinus screw in 78 cases of flatfoot children, and the satisfaction rate was as high as 96%, and no degradation occurred in the implant. Roth et al [24] treated 48 cases of flatfoot children by using screw implantation in tarsal sinus for subtalar joint retardation with an excellent rate of 91.5% at 5 years follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Before surgery After surgery P Score 61 (58-64) 83 (75-92) <.001 The first metatarsal angle,°35 19 (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25) <.001 Meary angle,°20 0 (0-3) <.001…”
Section: Discussionmentioning
confidence: 99%
“…It has been proposed that the screw's effect is not limited to mechanics, but proprioceptive alteration occurs, possibly accounting for contralateral improvement following surgery. 9,16,17 Many implants and operative techniques are currently used, and …”
Section: Discussionmentioning
confidence: 99%
“…Arthroereisis (calcaneo-stop procedure) consists of placing an implant within the sinus tarsi, limiting the mobility of the tarsus and preventing eversion of the subtalar joint. Although there are many short-term follow up studies reporting the efficacy of arthroereisis procedures, [8][9][10][11][12] long-term follow-up and comparative studies are lacking. 6 We aim to evaluate the long-term outcomes of the calcaneo-stop procedure in the treatment of flexible flatfoot in children, in one surgical centre.…”
Section: Introductionmentioning
confidence: 99%